Management Accounting Theory and Practice: Measuring the Gap in United States Businesses - John D. McLellan (Journal of Accounting, Business and Management (JABM), 2014)
In this study, we surveyed members of the Institute of Management Accountants (IMA) all Certified Management Accountants (CMA) working in the United States to determine, 1) the adoption rate of forty-one management accounting practices by their organizations, 2) to examine the degree of importance for the efficient operation of their business that CMA's placed on each management accounting practice and 3) to measure the variance between the two. The findings indicated a large discrepancy between what accountants consider effective management accounting tools and the use of those tools by their respective companies. Evidence suggested that businesses rely more on the traditional management accounting practices rather than the recently developed strategic practices such as activity based management and the use of the balanced scorecards. We measured the size of the gap between the use and importance of each management accounting tool and highlighted those MA tools that CMA's think could have a significant impact on improving business operations. This study updates the management accounting literature on the adoption rate of forty-one MA practices by businesses in the USA.